Polymorphisms in the TNFA and IL6 genes represent risk factors for autoimmune thyroid disease. - Cecília Durães (Public Library of Science (PLoS), 2014)
Background Autoimmune thyroid disease (AITD) comprises diseases including Hashimoto's thyroiditis and Graves' disease, both characterized by reactivity to autoantigens causing, respectively, inflammatory destruction and autoimmune stimulation of the thyroid-stimulating hormone receptor. AITD is the most common thyroid disease and the leading form of autoimmune disease in women. Cytokines are key regulators of the immune and inflammatory responses; therefore, genetic variants at cytokine-encoding genes are potential risk factors for AITD. Methods Polymorphisms in the IL6-174 G/C (rs1800795), TNFA-308 G/A (rs1800629), IL1B-511 C/T (rs16944), and IFNGR1-56 T/C (rs2234711) genes were assessed in a case-control study comprising 420 Hashimoto's thyroiditis patients, 111 Graves' disease patients and 735 unrelated controls from Portugal. Genetic variants were discriminated by real-time PCR using TaqMan SNP genotyping assays. Results A significant association was found between the allele A in TNFA-308 G/A and Hashimoto's thyroiditis, both in the dominant (OR = 1.82, CI = 1.37-2.43, p-value = 4.4×10(-5)) and log-additive (OR = 1.64, CI = 1.28-2.10, p-value = 8.2×10(-5)) models. The allele C in IL6-174 G/C is also associated with Hashimoto's thyroiditis, however, only retained significance after multiple testing correction in the log-additive model (OR = 1.28, CI = 1.06-1.54, p-value = 8.9×10(-3)). The group with Graves' disease also registered a higher frequency of the allele A in TNFA-308 G/A compared with controls both in the dominant (OR = 1.85, CI = 1.19-2.87, p-value = 7.0×10(-3)) and log-additive (OR = 1.69, CI = 1.17-2.44, p-value = 6.6×10(-3)) models. The risk for Hashimoto's thyroiditis and Graves' disease increases with the number of risk alleles (OR for two risk alleles is, respectively, 2.27 and 2.59). Conclusions This study reports significant associations of genetic variants in TNFA and IL6 with the risk for AITD, highlighting the relevance of polymorphisms in inflammation-related genes in the etiopathogenesis of AITD.